2015
DOI: 10.1128/iai.00015-15
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD1d-Restricted NKT Cells in the Clearance of Pseudomonas aeruginosa from the Lung Is Dependent on the Host Genetic Background

Abstract: dPseudomonas aeruginosa is an important human opportunistic pathogen, accounting for a significant fraction of hospital-acquired lung infections. CD1d-restricted NKT cells comprise an unusual innate-like T cell subset that plays important roles in both bacterial and viral infections. Previous reports have differed in their conclusions regarding the role of NKT cells in clearance of P. aeruginosa from the lung. Since there is significant strain-dependent variation in NKT cell number and function among different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…T cells orchestrate the activity of neutrophils and alveolar macrophages over the course of P. aeruginosa infection23. We found that at day 2, CD3 + and CD4 + T cell infiltrated the infected lungs to higher extents in C3H/HeOuJ resistant mice than in A/J susceptible ones (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…T cells orchestrate the activity of neutrophils and alveolar macrophages over the course of P. aeruginosa infection23. We found that at day 2, CD3 + and CD4 + T cell infiltrated the infected lungs to higher extents in C3H/HeOuJ resistant mice than in A/J susceptible ones (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Together these findings suggest a potentially important role for i NKT cells in mediating neutrophil responses for protection. Notably, in the pulmonary model of P. aeruginosa infection, a protective role for i NKT cells was later shown to only be true in BALB/c mice, and not C57BL/6 mice (Benoit et al 2015). This suggests different roles for the i NKT subsets, as BALB/c mice have more NKT2 cells, which might suppress neutrophil recruitment when activated, while C57BL/6 mice are more NKT1 subset biased.…”
Section: Inkt Cells Help Protect the Host From Infectionsmentioning
confidence: 99%
“…iNKT cells react also to a number of pathogens involved in airway infections, including Sphingomonas capsulata ( 107 ), Mycobacterium tuberculosis ( 108 ), Pseudomonas aeruginosa ( 109 , 110 ), Streptococcus pneumoniae ( 111 ) and Influenza A virus ( 112 , 113 ), via involvement of local mononuclear phagocytic cells, particularly macrophages. During M. tuberculosis infection in mice, iNKT cells are activated upon interaction with macrophages presenting mycobacterium-specific lipids ( 108 ) and help controlling the bacterial load via GM-CSF production ( 114 ), which may promote an inflammatory response that ultimately leads to bacterial clearance.…”
Section: The Lungsmentioning
confidence: 99%
“…A similar mechanism has been identified for P. aeruginosa , where iNKT cells stimulate increased phagocytic clearance of the bacteria in the lung by alveolar macrophages ( 109 ). Interestingly, in this context, iNKT cells have a stronger effect in controlling P. aeruginosa in BALB/c compared to C57BL6 mice ( 110 ). This difference can be explained by the different iNKT cell subsets that infiltrate the lungs of the two strains, as BALB/c mice contain an higher frequency of NKT1 subset compared to C57BL6 ( 24 , 115 ).…”
Section: The Lungsmentioning
confidence: 99%